Enhancing English Teaching in Elementary Schools: A Sociocultural Perspectives of Non-English Major Teachers’ Experiences - Purwanti, Eko; Prasanti, Sellin Yonica (Universitas Ahmad Dahlan, 2025)
English language has been introduced and taught to Indonesian students from elementary to higher education. In the context of Indonesian elementary education, the teaching of English often falls to homeroom teachers who lack formal qualifications in the language. This study explores the challenges and strategies of non-English major teachers in teaching English in Indonesian elementary schools using Sociocultural Theory framework. Utilizing qualitative approach and descriptive qualitative research design, a qualitative research method was employed, involving semi-structured interviews with six homeroom teachers from a public elementary school in Yogyakarta who teach English without the language background. The findings reveal six primary challenges: (1) problems with pronunciation, (2) lack of vocabulary, (3) mother tongue interference, (4) inadequate teaching skills, (5) large class sizes, and (6) diverse student characteristics. To address these challenges, these teachers adopted various strategies, including (1) participating in professional development programs, (2) engaging in peer discussions, (3) carrying out independent learning, (4) utilizing learning applications, (5) using learning media, and (6) forming study groups. These findings highlight the need for targeted support and training for non-English major teachers to enhance the quality of English education in Indonesian elementary schools.